Geodetic GPS-Based Pipeline Elevation Mapping Using RTK and Static Methods - Bangun Setyo Aji; Fahrudin Hanafi (JPG (Jurnal Pendidikan Geografi), 2026)
Pipeline elevation measurement is an essential stage in surveying and mapping oil and gas infrastructure to ensure that the pipeline’s position relative to ground contours meets safety and design standards. This study aims to apply and analyze the results of pipeline elevation measurements using Geodetic GPS with Real-Time Kinematic (RTK) and Static methods in the operational area of PT X. The RTK method was employed to obtain coordinate data of pipeline points efficiently in real time, while the Static method was applied to establish high-precision control points (benchmarks) to ensure vertical accuracy and data reliability. A total of 21 Bench Mark points and multiple Trunk Line (TL) observation points were measured along a 21-kilometer pipeline corridor. The collected data include geodetic coordinates, projected coordinates, and elevation values, which were further processed using AutoCAD software for contour generation, three-dimensional terrain modeling, and elevation profile extraction. The results indicate that the RTK method provides high operational efficiency with an average vertical accuracy of approximately ±2–3 cm, whereas the Static method achieves higher precision with deviations of around ±1 cm relative to benchmark references. The analysis also reveals a consistent elevation decrease from north to south, reflecting the natural topographic gradient of the study area. This information is critical for slope analysis, drainage planning, and pipeline stability assessment. The combination of both methods proved effective in producing accurate and consistent elevation data for topographic analysis. These findings demonstrate that the integrated RTK–Static approach is a reliable and practical solution for supporting precise pipeline surveying and engineering decision-making in complex terrain conditions. Furthermore, this study highlights the potential application of integrated geodetic methods as a practical learning resource in geography education, particularly in the fields of geospatial analysis and engineering surveying.